Toxicity management of regorafenib in patients with gastro-intestinal stromal tumour (GIST) in a tertiary cancer centre - Chamberlain, Florence (Clin Sarcoma Res, 2020)
BACKGROUND: Regorafenib is a multi-kinase inhibitor approved as third line treatment for metastatic GIST. Dose limiting toxicities are frequently seen and many patients require dose reductions. This study aimed to evaluate regorafenib toxicities and their management in a real-world GIST population. METHODS: Retrospective review of a prospectively maintained database identified 50 patients with GIST treated with regorafenib at our centre between March 2013 and September 2018. RESULTS: Median progression free survival (PFS) was 7.7 months [interquartile range (IQR) 2.8–14.4 months]. Median overall survival (OS) from start of regorafenib to death or last follow up was 15.7 months (IQR 9.2–28.4 months). Baseline median Eastern Cooperative Oncology Group (ECOG) performance status on starting regorafenib was 1. The main reason for discontinuing regorafenib was progressive disease (PD) (31/50 [62%]) rather than toxicity (10/50 [20%]). Grade 3–4 adverse events (AEs) were seen in 23/50 (46%) patients; palmar-plantar erythrodysesthesia (PPE) was most frequently seen (9/50 (18%)). Two patients died whilst on treatment with regorafenib from multi-organ failure secondary to sepsis (4%). Dose reductions were required in 19/50 patients (38%) and 8/50 (16%) patients started regorafenib at a lower dose band than the recommended dose (160 mg) due to comorbidities or concern over a higher individual risk of toxicity. CONCLUSION: Although PD was the main reason for discontinuing treatment, toxicity management and dosing of regorafenib remains critical. Median duration of treatment was longer compared to previous studies suggesting a durable clinical benefit with regorafenib with rigorous toxicity management.